Маловідомі факти з біографії С. Шварцбарда (до історії співробітництва з органами державної безпеки СРСР) - Савченко, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
The article is dedicated to the analysis of unknown facts of Shvartsbard’s biography about his cooperation with State Security of the USSR.